Isomer-specific regulation of metabolism and PPARγ signaling by CLA in human preadipocytes - J.Mark Brown (Journal of Lipid Research, 2003)
Trans-10,cis-12 conjugated linoleic acid (CLA) has previously been shown to be the CLA isomer responsible for CLA-induced reductions in body fat in animal models, and we have shown that this isomer, but not the cis-9,trans-11 CLA isomer, specifically decreased triglyceride (TG) accumulation in primary human adiopcytes in vitro. Here we investigated the mechanism behind the isomer-specific, CLA-mediated reduction in TG accumulation in differentiating human preadipocytes. Trans-10,cis-12 CLA decreased insulin-stimulated glucose uptake and oxidation, and reduced insulin-dependent glucose transporter 4 gene expression. Furthermore, trans-10,cis-12 CLA reduced oleic acid uptake and oxidation when compared with all other treatments. In parallel to CLA's effects on metabolism, trans-10,cis-12 CLA decreased, whereas cis-9,trans-11 CLA increased, the expression of peroxisome proliferator-activated receptor γ (PPARγ) and several of its downstream target genes when compared with vehicle controls. Transient transfections demonstrated that both CLA isomers antagonized ligand-dependent activation of PPARγ.Collectively, trans-10,cis-12, but not cis-9, trans-11, CLA decreased glucose and lipid uptake and oxidation and preadipocyte differentiation by altering preadipocyte gene transcription in a manner that appeared to be due, in part, to decreased PPARγ expression.